Phenotypic and genomic comparison of dominant and nondominant sequence-type of Acinetobacter baumannii isolated in China - Kong, Xiaoyang; Chen, Tao; Guo, Lihua; Zhou, Yanzi; Lu, Ping; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2023)
A. baumannii is a common clinical pathogen that often causes pneumonia and bloodstream infections in ICU patients. Sequence types (ST) are used to investigate the distribution and spread of A. baumannii. Biological characteristics such as virulence and resistance may play a role in A. baumannii becoming a specific dominant ST(DST,ST191, ST195 and ST208) strain. To characterize the biological, genetic, and transcriptomic differences between the DST and non-dominant ST(NST,ST462 and ST547,etc.) strains in A. baumannii, we performed several biological experiments and genetic, and transcriptomic analyses. The DST group displayed more resistance ability to desiccation, oxidation, multiple antibiotics, and complement killing than the NST group. However, the latter had higher biofilm formation ability than the former. The genomic analysis showed the DST group exhibited more capsule-related and aminoglycoside-resistant genes. Besides, GO analysis indicated that functions involved in lipid biosynthetic, transport, and the metabolic process were up-regulated in the DST group, while KEGG analysis manifested that the two-component system related to potassium ion transport and pili were down-regulated. In short, resistance to desiccation, oxidation, multiple antibiotics, and serum complement killing are important reasons for the formation of DST. Genes related to capsule synthesis and lipid biosynthesis and metabolism play an important role at the molecular level in the formation of DST.